2012
DOI: 10.1038/npp.2011.339
|View full text |Cite
|
Sign up to set email alerts
|

Differential Effects of Cocaine on Dopamine Neuron Firing in Awake and Anesthetized Rats

Abstract: Cocaine (benzoylmethylecgonine), a natural alkaloid, is a powerful psychostimulant and a highly addictive drug. Unfortunately, the relationships between its behavioral and electrophysiological effects are not clear. We investigated the effects of cocaine on the firing of midbrain dopaminergic (DA) neurons, both in anesthetized and awake rats, using pre-implanted multielectrode arrays and a recently developed telemetric recording system. In anesthetized animals, cocaine (10 mg/kg, intraperitoneally) produced a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
53
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 59 publications
(62 citation statements)
references
References 116 publications
(159 reference statements)
6
53
1
Order By: Relevance
“…36 adult male Wistar rats, weighing 250-300 grams, were implanted with a microelectrode array consisting of 8 platinum-iridium electrodes and designed so as to span the whole extent of the VTA (see details below and in Koulchitsky et al, 2012 Surgical and histological procedures were as described in detail elsewhere (Koulchitsky et al, 2012).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…36 adult male Wistar rats, weighing 250-300 grams, were implanted with a microelectrode array consisting of 8 platinum-iridium electrodes and designed so as to span the whole extent of the VTA (see details below and in Koulchitsky et al, 2012 Surgical and histological procedures were as described in detail elsewhere (Koulchitsky et al, 2012).…”
Section: Methodsmentioning
confidence: 99%
“…The recording site was then marked by an electrolytic lesion of the brain tissue through a previously implanted electrodes (1.0 mA cathodal current for 6 s), and animals were perfused intracardially with saline followed by a 4% formaldehyde saline solution. The brains were then removed and stored for histological examination (Koulchitsky et al, 2012).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Our work extends these findings to include a dopamine-suppressive action of an agent, LiCl, which produces a long-lasting aversive state Tomasiewicz et al, 2006). Dopamine neuron responses to stimuli can differ between anesthetized and awake subjects (Koulchitsky et al, 2012). We investigated the dopamine response to LiCl in both anesthetized and awake rats and consistently found that LiCl suppressed evoked dopamine release.…”
Section: Discussionmentioning
confidence: 59%